India's 2.42 Million Frontline Health Workers Enable Restoration of Health and Nutrition Service Delivery After Early COVID-19 Lockdowns. (7th June 2021) - Avula, Rasmi; Nguyen, Phuong; Ashok, Sattvika; Bajaj, Sumati; Kachwaha, Shivani; Pant, Anjali; Walia, Monika; Singh, Anshu; Paul, Anshuman; Singh, Ayushi; Kulkarni, Bharati; Singhania, Deepak; et al.
Abstract: Objectives: Modeling studies have estimated impacts of potential service delivery disruptions due to COVID-19 pandemic on maternal and child nutrition outcomes, but little is known about actual delivery status. We studied disruptions and restorations of health and nutrition services by frontline workers (FLWs) in India during COVID-19. Methods: We conducted phone surveys with 5500 FLWs in seven states between August–October 2020, asking about service delivery during April 2020 (T1) and in the August-October period (T2) and analyzed changes between T1 and T2. We also analyzed publicly available administrative data (AD) from 704 districts including the pre-pandemic period (T0) to examine disruptions and restoration of services. Results: Phone surveys suggest, in T1, opening of village centers, fixed day events, growth monitoring, and immunization services was <50% in several states. In T2, restorations of center-based services were seen, with increases of >33% in >= 3 states. Food supplementation was least disrupted both in T1 and T2. AD highlights geographic variability both in disruptions in T1 compared to T0 and restorations in T2. FLWs' adaptations to ensure service provision included home delivery (60 to 96%), ensuring physical distancing (33 to 86%), coordinating with other FLWs (7 to 49%), and using phone (∼2 to 65%). Challenges included personal fears, walking long distances, and beneficiaries' non-cooperation. Conclusions: Services to mothers and children were disrupted during lockdown and restored thereafter. Rapid policy guidance and local adaptations by a strong cadre of FLWs likely enabled service resumption. However, gaps remain, and more research is needed on use of services by clients. Funding Sources: Bill & Melinda Gates Foundation through POSHAN, led by International Food Policy Research Institute.